2013
DOI: 10.1021/jp4106585
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Study of Atomic Motion in A2B12H12 (A = Na, K, Rb, Cs): Anion Reorientations and Na+ Mobility

Abstract: To study the reorientational motion of icosahedral [B12H12]2– anions in A2B12H12 (A = Na, K, Rb, Cs) and the translational diffusion of Na+ cations in Na2B12H12, we have measured the 1H, 11B, and 23Na NMR spectra and spin–lattice relaxation rates in these compounds over the temperature range of 170–580 K. For cubic compounds K2B12H12, Rb2B12H12, and Cs2B12H12, the measured 1H and 11B spin–lattice relaxation rates are governed by thermally activated reorientations of the [B12H12]2– anions. The activation energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
142
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(164 citation statements)
references
References 25 publications
22
142
0
Order By: Relevance
“…This type of motion has never been observed in the complex transition metal hydrides, but has often been discussed in relation to the occurrence of fast ion conduction in alkali metal dodecahydro- closo -dodecaborates such as Na 2 B 12 H 12 . In this material, the first-order phase transition from the low-temperature monoclinic to the high-temperature cubic phase occurs near 520 K, which is accompanied by an increase of two orders of magnitude in the rate of reorientational jumps of the icosahedral [B 12 H 12 ] 2− anions with the fast translational diffusion of Na + ions35. Although we observed no obvious translational diffusion of Li + ions in our FPMD calculations because of the limited simulation time (12 ps) and the unit cell size (136 atoms), the significant rotational motions of [MoH 9 ] 3− ions, as observed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This type of motion has never been observed in the complex transition metal hydrides, but has often been discussed in relation to the occurrence of fast ion conduction in alkali metal dodecahydro- closo -dodecaborates such as Na 2 B 12 H 12 . In this material, the first-order phase transition from the low-temperature monoclinic to the high-temperature cubic phase occurs near 520 K, which is accompanied by an increase of two orders of magnitude in the rate of reorientational jumps of the icosahedral [B 12 H 12 ] 2− anions with the fast translational diffusion of Na + ions35. Although we observed no obvious translational diffusion of Li + ions in our FPMD calculations because of the limited simulation time (12 ps) and the unit cell size (136 atoms), the significant rotational motions of [MoH 9 ] 3− ions, as observed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous NMR, quasielastic neutron scattering (QENS), and electrochemical measurements of boron-based superhalogens have suggested there are highly mobile alkali cations (Li + , Na + ) and complex anion species (BH 4 -, B 10 H 10 -2 , B 12 H 12 -2 ) in alkali metal borane salts. [8][9][10][11][12][13][14][15][16][17] These studies also showed that various structural phase transitions occur in these materials that lead to more atomic disorder in the lattice at elevated temperatures. T hese transitions create vacancies that facilitate the enhanced cation and anion mobility.…”
Section: Introductionmentioning
confidence: 88%
“…B-H vibrations are readily studied by vibrational spectroscopy while the much lower energy transfers of stochastic reorientations are investigated by means of quasi-elastic neutron scattering. The structural dynamics of monometallic borohydrides have been extensively investigated by vibrational spectroscopy [28][29][30], solid state NMR spectroscopy [31][32][33][34][35], inelastic x-ray scattering IXS [36], inelastic neutron scattering INS [37], QENS [38][39][40] and recently by molecular dynamics assisted density functional theory (MD-DFT) [41,42]. The importance of the vibrational density of states for the stabilities of different polymorphs has also been discussed [43].…”
Section: Structural Dynamicsmentioning
confidence: 99%